The radio and IR counterparts of the ring nebula around HD 211564 - Cappa, Cristina Elisabeth (2010)
We report the detection of the radio and infrared (IR) counterparts of the ring nebula around the WN3(h) star HD 211564 (WR 152), located to the south-west of the H II region Sh2 132. Using radio continuum data from the Canadian Galactic Plane Survey, we identified the radio counterparts of the two concentric rings, of about 9 and 16 arcmin in radius, related to the star. After applying a filling factor f= 0.05–0.12, electron densities and ionized masses are in the range 10–16 cm−3 and 450–700 M⊙, respectively. The analysis of the H I gas emission distribution allowed the identification of 5900 M⊙ of neutral atomic gas with velocities between −52 and −43 km s−1 probably linked to the nebula. The region of the nebula is almost free of molecular gas. Only four small clumps were detected, with a total molecular mass of 790 M⊙. About 310 M⊙ are related to a small IR shell-like source linked to the inner ring, which is also detected in the MSX band A. An IRAS young stellar object candidate is detected in coincidence with the shell-like IR source. We suggest that the optical nebula and its neutral counterparts originated from the stellar winds from the Wolf–Rayet star and its massive progenitor, and are evolving in the envelope of a slowly expanding shell centred at Graphic of about 31 pc in radius. The bubble's energy conversion efficiency is in agreement with recent numerical analysis and with observational results.